Pedagogi Deep Learning sebagai Pendekatan Transformatif dalam Penguatan Critical Character dan Global Awareness: Deep Learning Pedagogy as a Transformative Approach in Strengthening Critical Character and Global Awareness - Sri Hariati; Alibin Rahmat; Tanti Irnanda; Komang Widiantara Saputra (ITScience (Information Technology and Science), 2026)
Social Sciences education in higher education plays a strategic role in developing students' critical thinking skills and global awareness as 21st-century citizens. However, learning that is still oriented towards mastering concepts often fails to optimize the development of critical character and global awareness. Therefore, a learning approach that encourages in-depth understanding, critical reflection, and the connection between knowledge and social reality is needed. This study aims to analyze the effects of deep learning pedagogy on students' critical character and global awareness in the Civics Study Program within social science education. The study used a quantitative approach with a quasi-experimental design employing a nonequivalent control group pretest-posttest design. The research sample was selected using purposive sampling, comprising an experimental group and a control group. Data were collected through questionnaires, observations, and documentation, then analyzed using descriptive statistics, normalized gain (N-Gain), and inferential statistical tests. The results showed that deep learning pedagogy had a positive effect on both research variables. The average N-Gain value of 0.60 for the critical character variable is in the medium category, while the value of 0.73 for the global awareness variable is in the high category. These findings indicate that deep learning is more effective at developing students' global awareness, particularly cross-cultural empathy, concern for global issues, and an orientation toward social action, without neglecting the development of critical thinking skills. Deep learning pedagogy has the potential to be a relevant alternative for supporting the development of critical character and global awareness within Citizenship Education in higher education.